The safety of tankers and single point mooring during loading operations - Paulauskas, Vytautas (Transport, 2009)
Single point mooring (SPM) is used when typical port facilities cannot be applied. Offshore platforms and terminals producing oil and gas are the places where SPM can be employed. Accidents with SPM equipment and ships occurring during loading or unloading operations are very dangerous and may cause serious losses due to the high prices of tankers and facilities and because of polluting the environment with poisonous materials. Any possibilities of decreasing risk and increasing safety are very important. This paper presents the analysis of dangerous situations with tankers and SPM, discusses theoretical basis for study and makes practical calculations and recommendations on decreasing accidence probability during loading operations. First published online: 27 Oct 2010